Adlai agenda a study on the brand development and promotion of Adlai (Coix Lacryma-Jobi L.) as a superfood among Metro Manila food and health enthusiasts - Magsanoc, Ma. Domenica Bengzon
Adlai is a local grain born to the same family as wheat, corn, and rice. It has been cultivated since ancestral times as a staple crop by the Subanen tribe in Mindanao, and contains three times the energy and nearly six times the protein content of its staple counterparts. Despite its superior qualities, the grain still remains unfamiliar to majority of the country's urban population.